Physicochemical Characteristics Of Kersen, Starfruit And Grapes For Fruit Vinegar With A Concentrations Acetobacter Aceti - Fitri Ida yanti; Dedin Finatsiyatull Rosida (UNIVED Press, Dehasen University Bengkulu, 2022)
Vinegar is a condiment made from sugar-containing materials through an alcoholic fermentation process followed by acetic acid fermentation. The principle in making vinegar is alcoholic fermentation and acetic acid fermentation. The use of kersen , starfruit dan grapes was chose because of its potential antioxidants vitamin C, flavonoids and polyphenols. The main quality criterion for vinegar is the acetic acid content. The purpose the determine the effect of the type fruit and concentration inoculum Acetobacter aceti on fruit vinegar characteristics. This study used a completely randomized design (CRD) two factors, type furit (kersen, starfuit and grapes) and concentration inoculum Acetobacter aceti (10%, 15%, 20%). The best treatment was the fruit vinegar with treatment starfruit and concentration inoculum Acetobacter aceti 15%, with the characteristic acetic acid content of 4.56%, pH 3.30, total soluble solids 3,10(°Brix), total sugar 0.76%. and alcohol content 2,04%.